2007
DOI: 10.4028/www.scientific.net/amm.10-12.913
|View full text |Cite
|
Sign up to set email alerts
|

The Investigations of Tool Wear and Wear Mechanism with Water Vapor as Coolants and Lubricants in Green Cutting

Abstract: In machining, coolants and lubricants improve machinability, increase productivity by reducing the tool wear and extend the tool life. However, the use of cutting fluid in metal working may seriously degrade the quality of environment. Green cutting is becoming increasingly more popular due to concern regarding the safety of the environment and operator health. The experimental investigations were carried out with cemented carbide tool in turning ANSI 304 stainless steel and applications of water vapor, CO2, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Thus, hydrogen atom free group and hydroxyl free group are easily formed. When oxygen comes into the cutting region, there may be reaction between oxygen and high energy electron [17]:…”
Section: The Boundary Lubrication Layer Forming Process In Cutting Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hydrogen atom free group and hydroxyl free group are easily formed. When oxygen comes into the cutting region, there may be reaction between oxygen and high energy electron [17]:…”
Section: The Boundary Lubrication Layer Forming Process In Cutting Anmentioning
confidence: 99%
“…The penetrating capillary speed can be calculated by Eq. (3) with water vapor as coolant and lubricant [17]:…”
Section: The Penetration Capillary Process With Water Vapor As Coolanmentioning
confidence: 99%
“…J.Y. Liu et al [19,20] introduce a new application of cooling and lubrication fluid in machining process. Using steam as the cooling and lubricant fluid can not only realize lubrication requirements and reduce cutting temperature, but also rare or no impact on the environment is.…”
Section: Cutting Temperaturementioning
confidence: 99%
“…Han and J.Y. Liu have deeply researched this cutting technique with applications of water vapor as coolant and lubricant, the results have shown that the cutting force was reduced about 30-40, 20-30 and 10-15 percent as compared with dry cutting, compressed air and oil water emulsion, the friction coefficient, the chip deformation coefficient and the surface roughness value were decreased, respectively, the cutting temperature was lowered in cutting C45 carbon steel by use of P10 cemented carbides tool (LIU, 2005).…”
Section: Introductionmentioning
confidence: 97%